2010
DOI: 10.1111/j.1365-3180.2010.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic variability of Striga gesnerioides populations parasitic on cowpea might be explained by a recent origin

Abstract: Dube M‐P & Belzile FJ (2010). Low genetic variability of Striga gesnerioides populations parasitic on cowpea might be explained by a recent origin. Weed Research50, 493–502. Summary Striga gesnerioides is an obligate root hemiparasitic plant that causes considerable yield losses to cowpea, an important crop legume of Sub‐Saharan Africa. The use of resistant cultivars is the easiest and most effective method to control the parasite. Several cowpea cultivars exhibiting resistance have been identified during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…in West Africa or Indigofera hirsuta L. in Florida. The low genetic diversity was explained on the basis of a common origin of the populations from a limited number of founder plants (Westwood & Fagg, ; Botanga & Timko, ; Dube & Belzile, ). In the case of the O. minor study, the authors also found two clearly different groups of populations, which suggested that they developed from two separate introduction events, as is probably the case for the Cuenca and the Guadalquivir Valley gene pools of O. cumana reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in West Africa or Indigofera hirsuta L. in Florida. The low genetic diversity was explained on the basis of a common origin of the populations from a limited number of founder plants (Westwood & Fagg, ; Botanga & Timko, ; Dube & Belzile, ). In the case of the O. minor study, the authors also found two clearly different groups of populations, which suggested that they developed from two separate introduction events, as is probably the case for the Cuenca and the Guadalquivir Valley gene pools of O. cumana reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that virulent populations do not share a common origin and strongly suggests that they might be the result of independent mutational events. Studies on S. gesnerioides populations collected on cowpea also showed lack of correspondence between genetic diversity and virulence groups in populations showing low genetic variability between and within populations (Dube & Belzile, ). Similarly, Semblat et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, thanks to the extreme host specificity of this species, and its autogamy, it has been possible to find crop varieties each differing in a single dominant gene, with complete immunity to one or more of its races (Li et al 2009;Singh et al 2006). One of the most valuable sources of resistance to be identified (from cowpea landrace line B301 with coincidental resistance to A. vogelii in Botswana) has proved effective against almost all the six or seven recognized races but not to a local race in Benin, which is thought to have evolved relatively recently (Dube and Belzile 2010). This and some other sources identified in West Africa have been used in breeding programs to produce varieties resistant to the local races of the parasite and with other desirable characters (Singh et al 2006).…”
Section: The Witchweedsmentioning
confidence: 99%
“…To date, at least 7 races (A–G) have emerged along with seven resistant genes ( Or1 – Or7 ). The same type of “arms race” could be observed in both species of witchweeds, S. asiatica [ 126 ] and S. gesnerioides [ 127 ].…”
Section: Evolution Of Host Specificities and Racesmentioning
confidence: 82%